2017
DOI: 10.1097/ta.0000000000001273
|View full text |Cite
|
Sign up to set email alerts
|

Improving mortality in trauma laparotomy through the evolution of damage control resuscitation

Abstract: Prognostic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 32 publications
2
40
3
Order By: Relevance
“…A mortality rate of 16.7% was found in the current cohort series, which is comparable to recent literature with mortality rates ranging from 7 to 17% [24][25][26]. In almost half of our patients, cause of death was considered neurological.…”
Section: Discussionsupporting
confidence: 85%
“…A mortality rate of 16.7% was found in the current cohort series, which is comparable to recent literature with mortality rates ranging from 7 to 17% [24][25][26]. In almost half of our patients, cause of death was considered neurological.…”
Section: Discussionsupporting
confidence: 85%
“…9   The difference in mortality between this study and those data appears to be due to fundamentally different patient populations. That study excluded patients who died within 30 minutes of surgical start and the data reported here included only patients whose time from ED to surgical start was ≤90 minutes.…”
Section: Discussioncontrasting
confidence: 52%
“…Use of this approach has been demonstrated to improve mortality, facilitate earlier abdominal closure, decrease healthcare costs, and decrease length of stay. 9,11,[15][16][17] These include hypotensive resuscitation techniques, early airway control, early use of blood and blood products, and other hemostatic agents.…”
Section: Tenets Of Dcrmentioning
confidence: 99%